[Pink Flowers Outside House in Husavik] - Streng, Evelyn Fiedler (1975)
Photograph of pink, pillar flowers along a house in Husavik, Iceland. The flowers sit along dark green bushes to the right of other purple flowers behind a yellow fence. The white building behind it has two, rectangular windows with open top sections. White lace curtains hang on the inside of the windows. The photograph is blurry.